2008
DOI: 10.1068/p5692
|View full text |Cite
|
Sign up to set email alerts
|

Change of Temporal-Order Judgment of Sounds during Long-Lasting Exposure to Large-Field Visual Motion

Abstract: The perceived temporal order of external successive events does not always follow their physical temporal order. We examined the contribution of self-motion mechanisms in the perception of temporal order in the auditory modality. We measured perceptual biases in the judgment of the temporal order of two short sounds presented successively, while participants experienced visually induced self-motion (yaw-axis circular vection) elicited by viewing long-lasting large-field visual motion. In experiment 1, a pair o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Our experiments revealed that the temporal perception of auditory events affected visual spatial information even if it was not a sufficiently large-field visual stimulus to be perceived as self-motion, whereas Teramoto et al ( 2008 ) reported that auditory TOJs were not affected by visual stimulus when their participants did not perceive self-motion. Thus, large-field visual stimuli are not always necessary to affect the temporal perception of auditory stimuli.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Our experiments revealed that the temporal perception of auditory events affected visual spatial information even if it was not a sufficiently large-field visual stimulus to be perceived as self-motion, whereas Teramoto et al ( 2008 ) reported that auditory TOJs were not affected by visual stimulus when their participants did not perceive self-motion. Thus, large-field visual stimuli are not always necessary to affect the temporal perception of auditory stimuli.…”
Section: Discussioncontrasting
confidence: 51%
“…Our aim in this paper is to present an example where visual spatial information can affect the TOJ tasks of auditory stimuli that are spatially uninformative unlike those in Teramoto et al ( 2008 ). The auditory stimuli in our experiments were a sequence of pure tones that were spatially uninformative, since the same auditory stimuli were presented to both ears.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Väljamäe (2009) demonstrates that moving sounds may enhance vection, an illusory feeling of self-motion induced by a constantly moving visual environment. Teramoto, Watanabe, and Umemura (2008) and Teramoto, Watanabe, Umemura, Matsuoka, and Kita (2004) show that in conditions of vection, people misjudge the temporal order of visual events, of sounds, and of tactile stimuli, but they have not examined the effect of vection on multisensory integration across any of these modalities. Väljamäe speculates that the directional congruence between a moving sound and moving visual environment may be crucial for the perception of motion but that any interaction between vision, audition, and other sensory modalities that could influence basic perception is poorly understood.…”
Section: Background Visual Motionmentioning
confidence: 99%
“…As noted in the Introduction, Väljamäe (2009) highlights the need for future research to understand more fully how optokinetic stimulation, vection, and auditory perception may interact. As also noted, Teramoto et al (2004Teramoto et al ( , 2008 have shown that under conditions of self-motion, people misjudge the temporal order of visual events, of sounds, and of tactile stimuli, but they have not examined the effect of self-motion on multisensory integration across any of these modalities. Further research is needed with procedures such as theirs to corroborate our findings and to examine the role of eye reflexes in such phenomena.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%